Corrections to “The Recent Technologies to Curb the Second-Wave of COVID-19 Pandemic” - M. Poongodi; Mohit Malviya; Mounir Hamdi; Hafiz Tayyab Rauf; Seifedine Kadry; Orawit Thinnukool (IEEE Access)
Presents corrections to the paper, (Corrections to “The Recent Technologies to Curb the Second-Wave of COVID-19 Pandemic”).